Menas i Afrodyta. „Dewocjonalia” z sanktuarium świętego Menasa - Kiss, Zsolt (Vox Patrum, 2015)
The article considers the ampullae and figurines produced in the Late Antiquity in the sanctuary of St. Menas in Abu Mina. Their forms and iconography are analised in the context of the earlier traditions of greco-roman art in Egypt, in which they are clearly rooted. Both the ampullae and the figurines can be considered as the manifestation of continuity of long established iconographical types in a new, Christian context.